High stability, single frequency, 300 mJ, 130 ps laser pulse generation based on stimulated Brillouin scattering pulse compression. (14th November 2014) - Zhu, Xuehua; Lu, Zhiwei; Wang, Yulei
Abstract: We obtained the output of single frequency laser pulses with an average pulse-width of 136 ps and the minimum of 123 ps based on stimulated Brillouin scattering pulse compression pumped by an 8 ns-pulse-width, 1064 nm-wavelength Q-switched Nd:YAG laser. The pulse-width stability of the output is about 4.1% while that of the pump pulses is about 1.1%, the highest energy conversion efficiency is about 85%, and the single pulse energy is above 300 mJ.